A comparative virulence analysis of Bipolaris sorokiniana based on host pathogen interaction and its toxin - RASHMI AGGARWAL, SAPNA SHARMA*, MEHDI JAHANI and (Indian Phytopathology, 2017)
Bipolaris sorokiniana is a hemibiotrophic fungus causing spot blotch of wheat and barley. The pathogen produces phytotoxins in culture that induces necrosis and play role in pathogenesis. Our results indicated the existence of variability based on host interactions with pathogen and toxin produced by the pathogen, separately. Twelve isolates of B. sorokiniana showed differences in disease reaction on wheat differential hosts. BS 25 was identified as most virulent and BS 7 as least virulent isolate. These two selected isolates further showed differences in the intensity of toxin band when resolved by thin layer chromatography (TLC). The grades of symptoms produced by the toxin of these isolates were similar to those produced by the respective pathogen isolates. Besides producing necrotic lesion on wheat the partially purified toxin caused necrotic lesions on barley, maize and sorghum studied using leaf infiltration bioassay.